2018
DOI: 10.1016/j.ijrobp.2018.01.072
|View full text |Cite|
|
Sign up to set email alerts
|

Ki67 Is an Independent Predictor of Recurrence in the Largest Randomized Trial of 3 Radiation Fractionation Schedules in Localized Prostate Cancer

Abstract: PurposeTo assess whether the cellular proliferation marker Ki67 provides prognostic information and predicts response to radiation therapy fractionation in patients with localized prostate tumors participating in a randomized trial of 3 radiation therapy fractionation schedules (74 Gy/37 fractions vs 60 Gy/20 fractions vs 57 Gy/19 fractions).Methods and MaterialsA matched case–control study design was used; patients with biochemical/clinical failure >2 years after radiation therapy (BCR) were matched 1:1 to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…In summary, by mRNA and protein levels, we showed that the upregulation is associated with the aggressiveness of PC. Our results corroborate similar observations in the literature, and with that, we propose that the Ki67 immunohistochemical assay should be incorporated into the prognostic evaluation of PC 9,[27][28][29][30] .…”
Section: Maiasupporting
confidence: 92%
“…In summary, by mRNA and protein levels, we showed that the upregulation is associated with the aggressiveness of PC. Our results corroborate similar observations in the literature, and with that, we propose that the Ki67 immunohistochemical assay should be incorporated into the prognostic evaluation of PC 9,[27][28][29][30] .…”
Section: Maiasupporting
confidence: 92%
“…These tissues including brain, lung, heart, liver, kidney and musculoskeletal tissues are characterised by very low proliferative indices with cells predominantly in G0 phase of the cell cycle, for which NHEJ is the dominant, if not exclusive, DSB repair system in humans 17 – 19 . This is also likely to be relevant in cancers such as breast and prostate with low proliferative indices 20 , 21 . Against this background, we explore the cellular basis of fractionation sensitivity in a range of normal human wild-type (WT)/mutant and malignant cell lines to test the hypothesis that fraction size sensitivity is modulated by TP53 and depends on error-prone NHEJ of radiation-induced DNA DSBs in G0/1 phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, Ki67 is not routinely used in clinical settings as a prognostic factor in the assessment of prostate cancer, likely due to lack of standardised assays and research into appropriate cut points for risk classification 68 . A more recent study by Wilkins et al 69 also reported Ki67 to be an independent prognostic factor of biochemical recurrence after radiation therapy, independent of established prognostic factors such as Gleason score, PSA and stage of disease. Similarly, Pollack et al 70 reported Ki67 to be a strong predictor of both distant metastasis and cause specific death in 537 patients receiving RT and androgen deprivation therapy (ADT), however this study used a cut-off of 11.3% to score Ki67 as "low" or "high", given the higher risk group of the patients involved in the study.…”
Section: Discussionmentioning
confidence: 92%